Biochemical predictors of death before discharge in cooled newborns following perinatal asphyxia - Sabina Terzić; Emina Vukas-Salihbegović; Verica Mišanović; Nedim Begić (Medicinski glasnik, 2022)
Aim: To analyse biochemical markers as possible predictors of death before discharge in cooled newborns following perinatal asphyxia. Methods: A total of 91 infants that underwent therapeutic hypothermia after perinatal asphyxia were included. Inclusion criteria for therapeutic hypothermia were Sarnat stage 2 or 3. Data were collected from medical histories regarding gender, gestational age, birth weight, Apgar and Sarnat score; additionally, gas analyses, liver and cardiac enzymes before, and in the first 12 hours after starting therapeutic hypothermia, were evaluated. The patients’ characteristics were compared between two groups, survivors and non-survivors. Results: Statistical difference was not found between groups regarding gender, gestational age, birth weight, delivery type, 1st and 5th minute Apgar score, seizures, alanine aminotransferase (ALT), creatine kinase (CK), troponin and fibrinogen level. Groups were significantly different regarding acid-base balance (p=0.012), base excess (BE) (p=0.025), lactate (p=0.002), aspartate aminotransferaze (AST), (p=0.011), lactate dehydrogenase (LDH) (p=0.006), activated partial thromboplastin clotting time (aPTT) (p=0.001) and international normalized ratio (INR) (p=0.001). Conclusion: Acid-base balance, BE, lactate, AST, LDH, aPTT and INR were significantly higher in the group of cooled newborns after perinatal asphyxia (non-survivors), and can serve as predictors of death before discharge. Combining diagnostic modalities raises a chance for accurate prediction of outcomes of asphyxiated infants.
Keywords: hypoxia; biochemistry; treatment